70th Anniversary of V.P. Malakhov - - - (RUDN Journal of Law, 2017)
The material focuses to the 70th anniversary of Doctor of Law, Professor of Moscow University of Ministry of Internal Affairs of Russia n. a. V.Ya. Kikot V.P. Malakhov, a specialist in the filds of philosophy of law, methodology of law, theory of law and state.